2023
DOI: 10.3390/md21110585
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Epigenetic Modification and High Hydrostatic Pressure on Polyketide Synthase Genes and Secondary Metabolites of Alternaria alternata Derived from the Mariana Trench Sediments

Qingqing Peng,
Yongqi Li,
Jiasong Fang
et al.

Abstract: The hadal biosphere is the most mysterious ecosystem on the planet, located in a unique and extreme environment on Earth. To adapt to extreme environmental conditions, hadal microorganisms evolve special strategies and metabolisms to survive and reproduce. However, the secondary metabolites of the hadal microorganisms are poorly understood. In this study, we focused on the isolation and characterization of hadal fungi, screening the potential strains with bioactive natural products. The isolates obtained were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
(54 reference statements)
1
0
0
Order By: Relevance
“…Low concentrations of SB did not induce significant biological effects, which may be related to the dose dependence of epigenetic modifiers [28]. In contrast, high concentrations of SB can indeed affect the synthesis of metabolites, leading to a decrease in carotenoid production, which is consistent with some research findings [29,30]. Additionally, after SB treatment, the biomass of the YM25079 strain decreased (Figure 1a), which matched the conclusions of another study in which the inhibition of HDAC was found to suppress yeast growth [31].…”
Section: Discussionsupporting
confidence: 89%
“…Low concentrations of SB did not induce significant biological effects, which may be related to the dose dependence of epigenetic modifiers [28]. In contrast, high concentrations of SB can indeed affect the synthesis of metabolites, leading to a decrease in carotenoid production, which is consistent with some research findings [29,30]. Additionally, after SB treatment, the biomass of the YM25079 strain decreased (Figure 1a), which matched the conclusions of another study in which the inhibition of HDAC was found to suppress yeast growth [31].…”
Section: Discussionsupporting
confidence: 89%